Contextualizing attitudes toward medical aid in dying in a national sample of interdisciplinary US hospice clinicians: hospice philosophy of care, patient-centered care, and professional exposure - Todd D. Becker; John G. Cagle; Cindy L. Cain; Joan K. Davitt; Nancy Kusmaul; Paul Sacco (Palliative Care and Social Practice)
Background: Despite extensive theoretical debate, empirical research on medical aid in dying (MAID) largely has disregarded broader, contextual factors as potential correlates of attitudes in hospice clinicians. Objective: Informed by institutional theory and neofunctional attitude theory, the objective of the current study was to quantitatively examine hospice clinicians’ attitudes toward MAID as functions of institutional characteristics relating to (Aim 1) individual adherence to hospice values and (Aim 2) state law. Design: We used a cross-sectional design. Methods: A national convenience sample of interdisciplinary hospice clinicians recruited through US professional membership associations self-administered an online survey. Measures included attitudes toward MAID, attitudes toward the hospice philosophy of care, attitudes toward the principle that hospice care should not hasten death, orientation toward patient-centeredness, professional exposure to working in a state where MAID is legal, and demographic characteristics. Data were analyzed via a partial proportional odds model. Results: The sample ( N  = 450) comprised hospice physicians (227 [50.4%]), nurses (64 [14.2%]), social workers (74 [16.4%]), and 85 chaplains (85 [18.9%]). Results of the partial proportional odds model indicated that professional exposure to working in a state where MAID is legal was significantly associated with over twice the cumulative odds of MAID support. Although neither orientation toward patient-centered care nor attitudes toward the hospice philosophy of care was significantly associated with attitudes toward MAID, results showed that disagreement with the narrower principle that hospice care should not hasten death was significantly associated with 6-to-7 times the cumulative odds of MAID support. Conclusion: Findings suggest that contextual factors—namely, the environments in which hospice clinicians practice—may shape attitudes toward MAID. Unanticipated results indicating that hospice professionals’ adherence to hospice values was not significantly associated with attitudes toward MAID underscore the need for further research on these complex associations, given previous theoretical and empirical support.